Manipulating Stacking Fault Energy to Achieve Crack Inhibition and Superior Strength-Ductility Synergy in an Additively Manufactured High-Entropy Alloy - Niu, Pengda (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.